The Role of Online Customer Reviews and Brand Equity in Shaping Purchase Decisions: A Comprehensive Exploration of Purchase Intention as a Mediator - Imaniar, Ghina; Ramdhansyah, Muhamad; Curatman, Aang; Rahmadi, Rahmadi (Journal of Economics and Business UBS, 2025)
Companies are required to compete fiercely to create and maintain consumer desires, because consumers continue to look for new things in the products and services they consume. The purpose of this study was to determine the role of online customer reviews and brand equity on purchasing decisions mediated by purchase intention. This study uses quantitative data analysis methods using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 software. Primary data was collected by distributing questionnaires to 160 consumers of the Erigo brand. Online customer reviews were found to have a positive impact on consumer purchase intentions, but did not directly influence purchase decisions. Instead, brand equity emerged as an important factor, which positively influenced purchase intentions and decisions. Furthermore, this study underscores the mediating role of purchase intention in bridging the effects of online customer reviews and brand equity on actual purchase decision behavior.